2019
DOI: 10.1183/13993003.01568-2018
|View full text |Cite
|
Sign up to set email alerts
|

Surgery or radiotherapy for stage I lung cancer? An intention-to-treat analysis

Abstract: IntroductionSurgery is the standard of care for early-stage lung cancer, with stereotactic ablative body radiotherapy (SABR) a lower morbidity alternative for patients with limited physiological reserve. Comparisons of outcomes between these treatment options are limited by competing comorbidities and differences in pre-treatment pathological information. This study aims to address these issues by assessing both overall and cancer-specific survival for presumed stage I lung cancer on an intention-to-treat basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Patients in the lobectomy group were significantly younger (67.9 vs. 76.6 years) and more frequently in lower Global Initiative for Chronic Obstructive Lung Disease (GOLD) classes with a significantly better performance status. As Deng et al suggest, this imbalance between the 2 populations is reported by many other retrospective analyses 3 and may favor the survival in the surgery group. These limitations can be overcome only by randomized prospective trials.…”
Section: To the Editormentioning
confidence: 84%
“…Patients in the lobectomy group were significantly younger (67.9 vs. 76.6 years) and more frequently in lower Global Initiative for Chronic Obstructive Lung Disease (GOLD) classes with a significantly better performance status. As Deng et al suggest, this imbalance between the 2 populations is reported by many other retrospective analyses 3 and may favor the survival in the surgery group. These limitations can be overcome only by randomized prospective trials.…”
Section: To the Editormentioning
confidence: 84%
“…Another retrospective study compared surgery and radiation therapy among patients with stage I lung cancer using an intention-to-treat analysis [16]. In that paper, multivariable Cox modeling revealed inferior overall survival in the SBRT group to that of the surgery group.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study [24] comparing 1102 patients treated with TA and 27,732 patients treated with SBRT, patients treated with TA had more comorbidities. This retrospective study also demonstrated that OS rates were comparable between TA and SBRT (1 year 85.4% vs. 86.3%, respectively, p ¼ .76; 2 years 65.2% vs. 64.5%, respectively, p ¼ .43; 3 years 47.8% vs. 45.9%, respectively, p ¼ .32; 5 years 24.6% vs. 26.1%, respectively, p ¼ .81).…”
Section: Comparison With Non-thermal Ablation Techniquesmentioning
confidence: 99%